2019
DOI: 10.1103/physrevlett.122.168101
|View full text |Cite
|
Sign up to set email alerts
|

Confinement-Induced Transition between Wavelike Collective Cell Migration Modes

Abstract: The structural and functional organization of biological tissues relies on the intricate interplay between chemical and mechanical signaling. Whereas the role of constant and transient mechanical perturbations is generally accepted, several studies recently highlighted the existence of longrange mechanical excitations (i.e., waves) at the supracellular level. Here, we confine epithelial cell mono-layers to quasi-one dimensional geometries, to force the establishment of tissue-level waves of well-defined wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 27 publications
3
78
1
Order By: Relevance
“…These results go along other studies performed on MDCK epithelial monolayers with a variety of theoretical approaches [8]. For example, various studies reported oscillations in vitro and they characterized them with various metrics yielding about the same length and time scales as ours [14][15][16][17][18][19][20]. Their theoretical approaches were based on Langevin harmonic oscillator, continuum active elastic tissue, phase field active Brownian particles, and Voronoi active Brownian model.…”
Section: Discussionsupporting
confidence: 83%
“…These results go along other studies performed on MDCK epithelial monolayers with a variety of theoretical approaches [8]. For example, various studies reported oscillations in vitro and they characterized them with various metrics yielding about the same length and time scales as ours [14][15][16][17][18][19][20]. Their theoretical approaches were based on Langevin harmonic oscillator, continuum active elastic tissue, phase field active Brownian particles, and Voronoi active Brownian model.…”
Section: Discussionsupporting
confidence: 83%
“…There exist numerous physics-based theoretical models that relate force and motion in a cell layer 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] . The formulation of those models may differ-for example, models have treated the cell layer as a continuum, a set of points on a lattice, a collection of polygons, or a group of self-propelled particles-but the models often have similar components, namely forces within the cell layer and at the cell-substrate interface balance with a viscous friction caused by cell motion.…”
Section: Background and Summarymentioning
confidence: 99%
“…These confined islands are one of multiple possible geometrical constraints, and the forces and motion may differ from other geometries such as larger cell layers and cell monolayers that are free to migrate outward, as in a wound healing assay. However, confinement has been considered in some theoretical models 7,10,21,22 , making this geometry a reasonable starting point. The data we provide include simultaneous measurements of cell velocities, cell-substrate tractions, and monolayer stresses.…”
Section: Background and Summarymentioning
confidence: 99%
“…Due to the complexity of collective behaviors, much effort has gone towards reductionist assays that restrict degrees of freedom and ensemble size to simplify analysis and interpretation. One powerful approach is to confine a tissue within predefined boundaries using micropatterning to create adhesive and non-adhesive regions (6)(7)(8)(9)(10)(11). Such confinement mimics certain in vivo contexts such as constrained tumors as well as aspects of compartmentalization during morphogenesis (12).…”
Section: Introductionmentioning
confidence: 99%